Perubahan Bunyi Asimilasi Bahasa Jawa Dialek Nganjuk dan Dialek Jombang (Kajian Linguistik Bandingan Historis) - Averyan Azhar Ghali, Akhmad Sauqi Ahya, Mu’minin (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Language is a tool for social interaction or human communication. Javanese is a regional language that is used as a daily language. This study examines Jombang Javanese and Nganjuk Javanese, because they have many similarities and also have some differences. With a geographical location that is only limited by the Brantas River, Nganjuk and Jombang Javanese languages have language differences. It is of interest to study the uniqueness of why with a geographical location that is close together, there can be differences in language. The difference tends to lead to differences in the sound of a language which is the focus of this research. The purpose of this study is to examine the form of sound changes in the Javanese dialect of Nganjuk and Jombang.The method used in this research is a qualitative method of literature study. The source of data in this research is taken from previous research that already exists. The data is in the form of words from two different languages. The method used in the data provision stage is the qualitative method of literature study, because what is taken in collecting data is by collecting data by understanding and studying theories from various literatures related to the research. The sound changes tend to be only in the form of replacement, subtraction, addition, and slight modification of letters or sounds. The Jombang dialect of Javanese also tends to emphasize words more often, while Nganjuk tends to smooth words more often.